Clinic-based SAMBA-II vs centralized laboratory viral load assays among HIV-1 infected children, adolescents and young adults in rural Zimbabwe: A randomized controlled trial. - Vinie Kouamou; Rhoderick Machekano; Tichaona Mapangisana; Caroline Maposhere; Reggie Mutetwa; Justen Manasa; Tinei Shamu; Kathy McCarty; Shungu Munyati; Junior Mutsvangwa; Mampedi Bogoshi; Dennis Israelski; et al. (PLoS ONE)
Background In Zimbabwe, children, adolescents and young adults living with HIV (CALWH) who are on public health antiretroviral therapy (ART) have inadequate viral load (VL) suppression. We assessed whether a clinic-based VL monitoring could decrease 12-month virologic failure rates among these CALWH. Methods The study was registered on ClinicalTrials.gov: NCT03986099. CALWH in care at Chidamoyo Christian Hospital (CCH) and 8 rural outreach sites (ROS) on long-term community-based ART were randomized (1:1) to 6 monthly VL monitoring by COBAS®Ampliprep®/Taqman48® HIV-1 at the provincial referral laboratory (PRL) as per standard of care (SOC) or by the clinic-based SAMBA II assay, Diagnostics for the Real World, at CCH. VL suppression, turn-around-time (TAT) for VL results, drug switching and drug resistance in second-line failure were assessed at 12 months. Results Of 390 CALWH enrolled 347 (89%) completed 12 months follow-up. Median (IQR) age and ART duration were 14.1 (9.7-18.2) and 6.4 (3.7-7.9) years, respectively. Over half (57%) of the participants were female. At enrolment, 78 (20%) had VL ≥1,000 copies/ml and VL suppression of 80% was unchanged after 12 months, with no significant difference between the SOC (81%) and the clinic-based (80%) arms (p = 0.528). Median (IQR) months to confirmatory VL result at CCH vs PRL was 4.0 (2.1-4.4) vs 4.5 (3.5-6.3) respectively; p = 0.027 at 12 months. Drug switching was documented among 26/347 (7%) participants with no difference between the median (IQR) time to switch in SOC vs clinic-based arms (5.1 (3.9-10.0) months vs 4.4 (2.5-8.4) respectively; p = 0.569). Out of 24 confirmed second-line failures, only 4/19 (21%) had protease inhibitor resistance. Conclusion In rural Zimbabwe, the clinic-based SAMBA II assay was able to provide confirmatory VL results faster than the SOC VL assay at the PRL. However, this rapid TAT did not allow for a more efficient drug switch among these CALWH.